HE LEAST DEVELOPED ZONES IN TOURISM FIELD AND THE BASIC WAYS TO DEPRIVE THEM OF RESUMING THAT CONDITION IN UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article is devoted to emerge the failures and lacks, as well as, peculiarities of tourism in disprospering places in the country. On the top of that possible offers are detected in order to flourish these failed borders into the best step. Some basic points have adduced to convert the heavy situation onto easy and positive one. That is the key point to utilize this article into practice.